Perancangan dan Pengembangan Plugin QGIS SPT untuk Menghitung Suhu Permukaan Tanah - Muhammad Rahmahalim; Fatwa Ramdani; Alfi Nur Rusydi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Land Surface Temperature (LST) is the temperature found in the outermost layer of the soil surface. Information about LST is very important because LST is a factor that can influence global climate change. There are several ways that can be used to obtain SPT data, one of which is to use data obtained from satellites using the help of a satellite image data processing application such as QGIS. There are various plugins provided by QGIS to help its users. Plugins are additional tools designed to deal with various problems encountered. However, there is currently no plugin that automatically calculates the LST algorithm. LST algorithm calculations performed on the QGIS application still use manual methods so to get LST data requires a complex steps to produce LST data. To facilitate the process of getting LST data, a plugin is needed that helps users to automatically calculate LST. In this case, the QGIS SPT plugin is built using the Python with the hope that it can simplify and speed up the process of calculating LST data.